Differential expression of 10 genes in the hypothalamus of two generations of rats selected for a reaction to humans - N. V. Klimova; I. V. Chadaeva; S. G. Shichevich; R. V. Kozhemyakina (Вавиловский журнал генетики и селекции, 2021)
Individual behavioral differences are due to an interaction of the genotype and the environment. Phenotypic manifestation of aggressive behavior depends on the coordinated expression of gene ensembles. Nonetheless, the identification of these genes and of combinations of their mutual influence on expression remains a difficult task. Using animal models of aggressive behavior (gray rats that were selected for a reaction to humans; tame and aggressive rat strains), we evaluated the expression of 10 genes potentially associated with aggressiveness according to the literature: Cacna1b, Cacna2d3, Drd2, Egr1, Gad2, Gria2, Mapk1, Nos1, Pomc, and Syn1. To identify the genes most important for the manifestation of aggressiveness, we analyzed the expression of these genes in two generations of rats: 88th and 90th. Assessment of gene expression levels was carried out by real-time PCR in the hypothalamus of tame and aggressive rats. This analysis confirmed that 4 out of the 10 genes differ in expression levels between aggressive rats and tame rats in both generations. Specifically, it was shown that the expression of the Cacna1b, Drd2, Egr1, and Gad2 genes does not differ between the two generations (88th vs 90th) within each strain, but significantly differs between the strains: in the tame rats of both generations, the expression levels of these genes are significantly lower as compared to those in the aggressive rats. Therefore, these genes hold promise for further studies on behavioral characteristics. Thus, we confirmed polygenic causes of phenotypic manifestation of aggressive reactions.